2018
DOI: 10.1111/gcb.14054
|View full text |Cite
|
Sign up to set email alerts
|

Digging deeper: A holistic perspective of factors affecting soil organic carbon sequestration in agroecosystems

Abstract: The global magnitude (Pg) of soil organic carbon (SOC) is 677 to 0.3-m, 993 to 0.5-m, and 1,505 to 1-m depth. Thus, ~55% of SOC to 1-m lies below 0.3-m depth. Soils of agroecosystems are depleted of their SOC stock and have a low use efficiency of inputs of agronomic yield. This review is a collation and synthesis of articles published in peer-reviewed journals. The rates of SOC sequestration are scaled up to the global level by linear extrapolation. Soil C sink capacity depends on depth, clay content and mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
239
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 520 publications
(295 citation statements)
references
References 185 publications
4
239
0
10
Order By: Relevance
“…Smith et al () estimate 1.6 Pg C/year as the maximum potential for enhanced agricultural management to mitigate CO 2 emissions to the atmosphere, whereas Zomer, Bossio, Sommer, and Verchot () estimate potential storage of 0.90–1.85 Pg C/year in croplands. At 2.45 Pg C/year, a recent new estimate by Lal () is slightly more optimistic. A separate analysis by scientists organized by the Nature Conservancy suggests that better soil management, within economic constraints, might store 0.41 Pg C/year, about 16% of the technical potential and only a small fraction (~4%) of our current fossil fuel emissions (Griscom et al, ).…”
mentioning
confidence: 91%
“…Smith et al () estimate 1.6 Pg C/year as the maximum potential for enhanced agricultural management to mitigate CO 2 emissions to the atmosphere, whereas Zomer, Bossio, Sommer, and Verchot () estimate potential storage of 0.90–1.85 Pg C/year in croplands. At 2.45 Pg C/year, a recent new estimate by Lal () is slightly more optimistic. A separate analysis by scientists organized by the Nature Conservancy suggests that better soil management, within economic constraints, might store 0.41 Pg C/year, about 16% of the technical potential and only a small fraction (~4%) of our current fossil fuel emissions (Griscom et al, ).…”
mentioning
confidence: 91%
“…Previous studies on SOC changes responding to different management practices mainly focused on the topsoil due to the higher SOC concentration and the sensitive responses of SOC to environmental changes at this soil depth [32]. However, many more studies reported that focusing on subsoil would give an accurate estimation of changes in SOC concentration and storage [33,34]. Our study showed that the SOCS at 0-20 cm depth in the LEY, PUC, ECH, SUA, and CHL treatments accounted for 60.567%, 62.669%, 54.627%, 58.668%, and 57.467%, respectively, of total SOCS at the 0-50 cm depth (Table 3).…”
Section: Effect Of Vegetation Type On Soc Concentration and Storagementioning
confidence: 99%
“…Interest in organic amendment application to rangelands has been increasing in parallel to soil health efforts in croplands, bolstered by growing interest in using these materials to restore degraded rangelands, a need that may expand as global changes increasingly challenge these lands (Huang et al, ). However, practices seeking to increase soil C might be less effective on untilled rangelands than on croplands, pastures, or restoration sites such as abandoned mines, since prior soil disturbance of most cropland, pasture, or restoration sites would decrease soil C pools, enabling greater proportional increases in soil C pools following amendments (Lal, ; Larney & Angers, ). In general, the efficacy and outcomes of this practice on rangelands are relatively poorly studied, and the potential for negative environmental consequences are higher in rangelands than croplands due to their starkly different ecology and management context, as detailed below.…”
Section: Introductionmentioning
confidence: 99%